The Impact of Work Fatigue on Incident Risk in the Ship Crew - Ananda, Vemas Risky; Anita, Kristin; Prasetya, Tri Budi (Politeknik Ilmu Pelayaran Semarang, 2025)
Occupational fatigue is a significant factor that increases the risk of accidents in the shipping industry, especially for crew members working under high stress and strenuous operational conditions. Several incidents, such as crew members falling into the water and fingers being pinched in barge bolder, demonstrate the link between fatigue and occupational risk. This study aims to identify the causes of fatigue in ship crew, its impact on work safety, and prevention efforts in the ship’s operational environment. The research method used is descriptive qualitative method to determine the impact of fatigue on the risk of incidents on ship crews. This research uses data collection techniques with observation, documentation, interviews with safety officers, crew, and ship captains and literature studies. Data analysis is carried out through several stages, such as data collection, data reduction, data presentation, and conclusion drawing or verification. For validity, researchers use triangulation of sources and triangulation of techniques so that the data is declared valid. The results of the study indicate that work fatigue in the crew of PT Dian Ciptamas Agung is influenced by irregular working hours, lack of adequate rest time, and high workload pressure. These conditions contribute to the increasing risk of incidents on board. To overcome this, systematic steps are needed by the company such as rearranging work schedules and rest times, providing safety training for crew, and monitoring work duration. Evaluation and strengthening of fatigue management policies are key to efforts to minimize the risk of incidents on an ongoing basis.